2014
DOI: 10.1186/1471-2393-14-266
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate prenatal care utilization and associated factors in São Luís, Brazil

Abstract: BackgroundOver the last decades there has been a reduction of social inequalities in Brazil, as well as a strong expansion of health services, including prenatal care. The objective of the present study was to estimate the rate of inadequate prenatal care utilization and its associated factors in São Luís, Brazil, in 2010 and to determine whether there was a reduction of inequity in prenatal care use by comparing the present data to those obtained from a previous cohort started in 1997/98.MethodsData from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
25

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 42 publications
2
29
0
25
Order By: Relevance
“…As per this finding, the likelihood of using ANC increased along with the change in the household wealth index from poor to rich. This finding was revealed in previous studies that were conducted in Brazil, India and other developing countries [13,22,25]. In fact, Ethiopia has declared ANC services to be provided for free to all mothers in order to avoid the financial barrier those women could encounter while seeking the care.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…As per this finding, the likelihood of using ANC increased along with the change in the household wealth index from poor to rich. This finding was revealed in previous studies that were conducted in Brazil, India and other developing countries [13,22,25]. In fact, Ethiopia has declared ANC services to be provided for free to all mothers in order to avoid the financial barrier those women could encounter while seeking the care.…”
Section: Discussionmentioning
confidence: 69%
“…In the data selection step, a total of 10 attributes were selected, assuming to have a frequent pattern with ANC utilization based on the review from the previous literature dimensions in which ANC utilization was affected [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. The dependent variable of this study is ANC utilization ("Yes" if the mother receives ANC for at least one time during a pregnancy, or else "No").…”
Section: Data Selection and Cleaningmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of FHS in the provision of antenatal care was also noticed for other localities in Brazil. Bernardes et al [33] showed that FHS was effective in reducing prenatal care inadequacy. The authors compared prenatal care utilization in São Luis, Maranhão (Northeast region), before (1997/1998) and after FHS implementation (2010).…”
Section: Discussionmentioning
confidence: 99%
“…Related to antenatal care FHS has contributed to scale up the coverage and to promote an equal access to adequate care [32, 33]. However, Brazil has some of the greatest income inequalities in the world [34].…”
Section: Introductionmentioning
confidence: 99%